Common Difficulties in English Speaking Encountered by Primary School Students - Widagdo, Arif (Proceedings of the UR International Conference on Educational Sciences, 2018)
Speaking is the active use of language to express meaning, and for young learners (especially primary school students), the spoken language is the medium through which a new language is encountered, understood, practiced, and learnt. Rather than oral skills being simply one aspect of learning language, the spoken form in the primary studentsâ classroom acts as the prime source of language learning. However, speaking problems can be major challenges to effective foreign language learning and communication. English as foreign language (EFL) learners, no matter how much they know about the English language, still face many speaking difficulties. Many studies have indicated that oral language development has largely been neglected in the classroom, and most of the time, oral language in the classroom is used more by teachers than by students. However, oral language, even as used by the teacher, hardly ever functions as a means for students to gain knowledge and explore ideas. To develop the knowledge to deal with oral communication problems in an EFL context, researchers first need to know the real nature of those problems and the circumstances in which âproblemsâ are constructed.